2020
DOI: 10.25134/ieflj.v6i1.2637
|View full text |Cite
|
Sign up to set email alerts
|

The Teaching of Writing Recount Texts by Utilizing Padlet

Abstract: Writing has always been beneficial for those who master it. Albeit its virtues, it is subject to investigation due to issues concerning its derisory tasks, its complexity, and its arid learning activities. Based upon the issues, this study is aimed at portraying how English teachers teach students writing recount texts by integrating Padlet into their classroom. Involving one English teacher and a class of 25 students, this study obtained the data through observation of four class meetings. The data were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…The results obviously showed that Padlet was an effective tool for learning vocabulary within the CLT environment and learner-centered settings, which is consistent with the findings of previous studies in this topic such as Lestari and Kurniawan (2018), Algraini (2014) Saepuloh and Salsabila (2020). In addition other researchers (e.g., Awaludin & Karim, 2017;Haris et al, 2017;Toti, 2018) also described it as an effective tool with a significant role in improving students' language skills as well as contributing to their positive attitudes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results obviously showed that Padlet was an effective tool for learning vocabulary within the CLT environment and learner-centered settings, which is consistent with the findings of previous studies in this topic such as Lestari and Kurniawan (2018), Algraini (2014) Saepuloh and Salsabila (2020). In addition other researchers (e.g., Awaludin & Karim, 2017;Haris et al, 2017;Toti, 2018) also described it as an effective tool with a significant role in improving students' language skills as well as contributing to their positive attitudes.…”
Section: Discussionsupporting
confidence: 90%
“…Due to these benefits, numerous surveys of attitudes toward Padlet have found positive views of the application, and researchers found that utilizing Padlet in the sphere of education increases student interest and motivation (Awaludin & Karim, 2017;Haris, Yunus, & Badusah, 2017;Saepuloh & Salsabila, 2020;Toti, 2018). Lestari and Kurniawan (2018) conducted a study Arab World English Journal www.awej.org ISSN: 2229-9327 363 that aimed to investigate the effectiveness of Padlet with regard to improving students' mastery over writing; the researchers designed their experiment in two phases and each phase included observations of student "planning, implementing, observing, and reflecting."…”
Section: Using Padlet As a Teaching Toolmentioning
confidence: 99%
“…It is because in writing recount text, the students should be aware in using the schematic structure of recount text including orientation, record of events, and reorientation (Anderson & Anderson, 1998). Besides, the students should apply the linguistic features of recount in their text, including specific participants, circumstance of time and place, first person, additive conjunction, material process, and past tense (Gerot & Wignell, 1995in Saepulloh, 2020. So those three aspects are the problems of the students in writing recount text.…”
Section: Discussionmentioning
confidence: 99%
“…The fragments presented above were not provided with detailed explanations. According to Saepuloh and Salsabila (2020), the series of events should involve chronological steps and comment which expresses response from the writer. Hanafi (2019) added that it is usually presented in sequence by describing the events or activities chronologically.…”
Section: Reorientationmentioning
confidence: 99%